O PT e a Unidade Partidária como Problema - Lacerda Alan Daniel Freire de (Dados: Revista de Ciências Sociais, 2002)
This article analyzes the issue of party unity, investigating the factors that favor or discourage party breaks. Three independent variables are proposed, forming a model that seeks to evaluate the possibilities for splitting or maintaining party organization. The variables are the intra-partisan institutional arrangement, internal ideological dissent, and the electoral costs of a split. The model is applied to the case of the Workers' Party (PT), seeking to evaluate which factors are the strongest in this party, those leading to a split or those favoring maintenance of unity in the party's organization. The study draws on various data sources, including party documents and bylaws, theses proposed by party factions, and election results, covering four national events in the 1990s. The study contends that intra-partisan institutional arrangements and the electoral costs of a split have strongly discouraged any break in the PT as a political party, and that if all else remains constant, these factors will continue to produce the same effects in the foreseeable future.